Optimizing fixed income portfolio using value at risk measures - Consolacion, Aldryn G. (Quezon City College of Science, University of the Philippines, 2007)
In this study, we will investigate how insurance firms can take favorable interest income through proper management of their fixed income portfolio. We will discuss how various techniques of risk management particularly the use of Value at Risk measures can be a necessary step to minimize investment losses. Further, we will emphasize the importance of data analysis and optimization techniques in handling various financial instruments commonly used by insurance firms to sustain profitable income in the future. We will limit our analysis to Philippines based fixed income markets, equity securities and government bonds. Major tools in statistics in tandem with optimization techniques shall lead the overall methodology of this research.
Thesis (M.S. Applied Mathematics)--University of the Philippines Diliman
Keywords: Fixed-income securities -- Philippines; Portfolio management -- Philippines; Investment advisors -- Philippines